2015
DOI: 10.1071/an14449
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and manipulating diet choice in grazing animals

Abstract: Conventional models of foraging, such as optimal foraging theory, generally take the univariate approach to explain the decisions of consumers on the basis of the intrinsic properties of foods, including nutrient concentration and abundance. However, the food environment is inherently diverse and, as a consequence, foraging decisions are influenced by the interactions among multiple food components and the forager. Foraging behaviour is affected by the consumer’s past experiences with the biochemical context i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 97 publications
0
37
0
4
Order By: Relevance
“…In addition, sheep exhibited a preference for previously grazed plants and areas, not only related to their nutritional status, but also to habitual behavior, as evidenced by the presence of trails related to presence of water and shade, and also for plants they have grazed before (O'Connor, 1992). Their preference for certain species is partly due to previous experience and what they have learned (Villalba et al, 2015). In our study, the individual sheep in the grazing flocks in 2008 and 2010 were completely different, which may indicate that sheep has a strong ability to identify good forage quality patches, rather than indicating that sheep retained a memory for previously grazed sites.…”
Section: Effects Of Grazing Intensity and Patch Types On Spatial Biommentioning
confidence: 95%
“…In addition, sheep exhibited a preference for previously grazed plants and areas, not only related to their nutritional status, but also to habitual behavior, as evidenced by the presence of trails related to presence of water and shade, and also for plants they have grazed before (O'Connor, 1992). Their preference for certain species is partly due to previous experience and what they have learned (Villalba et al, 2015). In our study, the individual sheep in the grazing flocks in 2008 and 2010 were completely different, which may indicate that sheep has a strong ability to identify good forage quality patches, rather than indicating that sheep retained a memory for previously grazed sites.…”
Section: Effects Of Grazing Intensity and Patch Types On Spatial Biommentioning
confidence: 95%
“…Boissy and Lee (2014) suggest three ways that cognitive and emotional enrichment can be achieved: (1) signalling a reward in advance, (2) providing a reward that is greater than expected, and (3) providing the animal with the ability to control fulfilment of 'wants' and 'likes'. However, experience of French shepherds suggests that too great a predictability of the timing of feed rewards can distract goats from engaging in normal grazing activities and reduce overall feed intake while they await the reward (Villalba et al 2015). Thus, complexity in the reward structure is needed to avoid frustration from unfulfilled expectations (Greiveldinger et al 2011).…”
Section: Managing Animals To Enhance Resiliencementioning
confidence: 99%
“…Many studies on animal nutrition and ethology suggest that feed intake of livestock on a pasture could be regulated by plant characteristics, such as structure, morphology and secondary chemistry (Cooper et al 1994;Owen-Smith 1994;Molle et al 2009;Villalba et al 2015). Moreover, studies have demonstrated that livestock have greater intake and perform better when they are provided with a mix of forage (Pennings et al 1993;Bernays et al 1994;Burritt & Provenza 2000;Marsh et al 2006).…”
Section: Introductionmentioning
confidence: 99%